Dyes and their Importance: A Review - Yadav, Chandradip Kumar; Basnet, Nabin (Damak Campus Journal, 2023)
The global market for pigments and dyes is forecast to reach 9.9 million tons and 26.53 billion by the year 2017, driven by the growth in key end-use industries. Before synthetic dyes and pigments were discovered, limited number of natural colorant has been obtained from plants, animals and minerals. The classification of colorants has become mandatory due to huge increase in kind and number of colorants. For this reason, colorants are classified based on their structure, source, color, solubility and application methods. In this chapter, dyes will be investigated in two different groups as accordance with chemical structures and application methods. The basic classification groups were determined as azo, anthraquinone, indigo, phthalocyanine, sulfur, nitro and nitroso dyes by considering their chemical structures. According to application method, they were grouped as reactive, disperse, acid, basic, direct, and vat dyes. However, the classification of pigments as organic and inorganic pigments is also regarded as an appropriate way.